(3GdCSGdjH hGdCOhGJ hGdESJNOeGJ GdYedjIs - (3eMeO(B, (3eWQs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2006)
(3CZQGV hebheGJ GdJMdjd GdeGdj(B- (3eONd hCSGdjH GdJMdjd GdeGdj(B- (3JaSjQ eDTQGJ hfJGFL GdJMdjd GdeGdj (B-(3BKGQ GdJVNe GdEbJUGOj Ydi eUOGbjI GdfSH GdeGdjI(B- (3JMdjd GdJOabGJ GdfbOjI(B- (3JMdjd GdJYGOd(B- (3GdbhGFe GdeGdjI GdeJhbYI hJMdjd GdeMGSHI(B- (3GdJMdjd GdeGdj dCZQGV GdJehjd(B- (3GdJMdjd GdeGdj dCZQGV GdCfOeGL(B- (3JMdjd GdEFJeGf(B- (3GdEJLGgGJ GdMOjKI aj GdJMdjd GdeGdjs
(3GdeQGLY U(B.456s
Keywords: (3GdJehjds; (3GdeGdjI(B-(3GdJMdjds